The Use of Six Sigma Concepts at State and Private Jordanian Universities - Ahmed Y. Dudien; Majed A. Musaidah (University of Science and Technology, Yemen, 2014)
The Use of Six Sigma Concepts at State and Private Jordanian UniversitiesAbstract: This study aims to find out howto use Six Sigma concepts in the government and private Jordanian universities. Also it aims to illustrate the importance of application in the continuous improvement of services and educational processes in these universities; in addition to that, it aims to identify the obstacles that prevent the use of the concepts of Six Sigma at these universities. To achieve the objectives of this study, a questionnaire was designed and distributed to a sample of the population which included (269) faculty members and administrators of government and private Jordanian universities. Following the required statistical analysis, the findings of this study indicated a recent application of the concepts of Six Sigma at these universities, and there is no clear example can be adopted by the universities on the concepts of Six Sigma, in addition to that the study indicated weakness of qualified human resources, and limited financial resources, in these universities which prevent the application of Six Sigma concepts. This study recommends the importance of using the concepts of Six Sigma in government and private Jordanian universities, for the purpose of continuous improvement in its services and educational operations, as well as to be used as a statistical tool to measure problems and defects of the educational processes, to be able to remove or close to the zero point or free from these defects. Keywords: Six Sigma, Jordanian universities, DMAIC methodology, Total Quality Management.